Psychological Readiness to Return to Sport at 6 Months is Higher After Bridge-Enhanced ACL Repair than Autograft ACL Reconstruction. Issue 5 (31st May 2022) - Sanborn, Ryan M.; Badger, Gary J.; Yen, Yi-Meng; Murray, Martha M.; Christino, Melissa A.; Sant, Nicholas; Barnett, Samuel; Fleming, Braden C.; Kramer, Dennis E.; Micheli, Lyle J.
Background: Prior clinical studies have shown that psychological factors have a significant effect on an athlete's readiness to return to sport following ACL reconstruction (ACLR). Hypothesis/Purpose: We hypothesized that patients who underwent Bridge-Enhanced ACL Repair (BEAR) would have higher levels of psychological readiness for return to sport compared to ACLR, and baseline characteristics and 6-month outcomes would predict psychological readiness at 6 months following an ACL surgical procedure. Methods: 100 patients (median age 17 years; median pre-operative Marx Activity Score 16) with complete mid-substance ACL injuries were randomized to either the BEAR procedure (n=65) or autograft ACLR (n=35) and underwent surgery within 45 days of injury. Objective, functional, and patient-reported outcomes, including the ACL-Return to Sport after Injury (ACL-RSI) scale, were assessed at 6 months, 12 months, and 24 months. Results: Patients who underwent the BEAR procedure had significantly higher ACL-RSI scores at 6 months compared to those that underwent an ACLR (71.1 vs 58.2, p=.008), and scores were similar at 12 months and 24 months. Baseline factors independently predictive of higher ACL-RSI scores at 6 months were having a BEAR procedure and participating in Level 1 sports prior to injury, which explained 15% of the variability in ACL-RSI scores. Regression analysis of baseline and 6-month outcomes as predictors indicated that the IKDC score at 6 months explained 45% of the 6-month ACL-RSI variance. Subsequent analysis, with IKDC excluded from the model, indicated that decreased pain, increased hamstring and quadriceps strength in the surgical limb, and decreased side-to-side difference in AP knee laxity were significant predictors of a higher ACL-RSI score at 6 months, explaining 34% of the variability in ACL-RSI scores. Higher ACL-RSI scores at 6 months were associated with earlier clearance to return to sports. Conclusion: Patients who underwent the BEAR procedure had higher ACL-RSI scores at 6 months after surgery. Better ACL-RSI scores at 6 months were related most strongly to higher IKDC scores at 6 months. Lower pain levels, better muscle recovery, and less knee laxity at 6-months post-surgery were also associated with improved ACL-RSI scores at that time point.